Characterization and mechanical properties of in-situ titanium diboride fibre reinforced aluminium-copper alloy composites - Ramli, Rosmamuhamadani (2016)
Aluminium (Al) based in-situ metal matrix composites (MMCs) have better properties and performance when compared to ex-situ MMCs. Al-MMCs alloys are quite attractive due to their low density, their capability to be strengthened by precipitation, their good corrosion resistance, high thermal and electrical conductivity. Aluminium-copper (Al-Cu) alloys is the one of most MMCs have important high-strength Al alloys. The Al casting alloys, based on the Al-Cu system are widely used in light-weight constructions and transport applications requiring a combination of high strength and ductility. Recently, in-situ techniques have been developed to fabricate Al-based MMCs, which can lead to better adhesion at the interface and hence better mechanical properties. These in-situ routes provide many advantages such as the in-situ formed reinforcement phases are thermodynamically stable, disperse more uniformly in matrix, free of surface contamination and leading to stronger particle matrix bonding.In this research, Al-Cu master alloy was reinforced with 1 to 6wt.% titanium diboride (TiB2) obtained from salts route reactions which were potassium hexafluorotitanate (K2TiF6) and potassium tetrafluoroborate (KBF4) salts. The salts route reaction process done at 800 °C.. Then the Al-Cu alloy has characterized on the mechanical properties and microstructure characterization. The Instron tensile machine, Vickers and Rockwell hardness tester, and pin on-disc machine were used to characterize the tensile, hardness and wear properties of Al-Cu alloys respectively. Salts spray fog test and Gamry-electrode potentiometer were used to determine the corrosion rate of this alloys. From results obtained, the increasement of TiB2 contents will increased the value of tensile and hardness properties to Al-Cu alloy. The study also indicates that TiB2 particles have giving improvement the wear performance of the Al–6wt.%Cu alloy. For a constant load and sliding speed, the wear rate decreases as a function of amount of TiB2 in the composite. However, addition of TiB2 particle to the Al–6 wt%.Cu matrix has show the coefficient value of wear decreases regardless of applied load. Microstructure from scanning electron microscope (SEM) shows the composites synthesized using in-situ techniques exhibit the presence a uniform distribution of reinforcement that tends to be fine, and associated with a clean interface with the metallic matrix. Morphology observed that the particles of the TiB2 phase show a hexagonal morphology with straight and sharp edges. In order to achieve a good mechanical and wear properties it is important to control Al3Ti phase formation during the synthesis of in-situ Al-Cu/TiB2 composites. In corrosion test that conducted by salt spray fog and Gamry-electrode potentiometer, Al-Cu with composition of 3wt.%TiB2 gave the good properties in corrosion characterization compare to cast Al-Cu alloy itself. As comparison, Al-Cu with 3wt.%TiB2 gave the lowest value of corrosion rate, which means alloy has a good properties in corrosion characterization.The results obtained show that in-situ Al-Cu alloy composites containing different weight of TiB2 phase were synthesized successfully by the salt-metal reaction method and the particles were distributed evenly in the matrix of the composites.